Efficacy of Turmeric Rhizome Infusion (Curcuma longa L.) on Mortality of Aedes sp. Mosquito Larvae - Salsabila Yunita Kurniawan; I Nyoman Bagus Aji Kresnapati; Novitarini Novitarini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Aedes aegypti and Aedes albopictus are mosquito vectors that are thought to be the cause of Dengue Hemorrhagic Fever (DHF), especially in Indonesia, because it is a tropical climate area, and the rate of disease transmission due to mosquitoes is high. Besides that, Indonesia is known for being rich in plant species that can be used as natural larvicides. Turmeric rhizome (Curcuma longa L.) is a plant that contains secondary metabolites that can be used as larvicide. The purpose of this study was to test the effectiveness of turmeric rhizome infusion (Curcuma longa L.) on the mortality of Aedes aegypti and Aedes albopictus mosquito larvae. In this study, turmeric rhizome (Curcuma longa L.) infusion was used at concentrations of 25%, 50%, and 75%, as well as the positive control (abate drug) and the negative control (aquadest). The Kruskal–Wallis test results showed a probability value (p-value) of 0.001 (p<0.05) in both Aedes aegypti and Aedes albopictus larvae, indicating a significant difference between treatment groups, especially between the positive control and the 75% concentration of turmeric rhizome infusion treatment. Furthermore, the Mann–Whitney U test results showed that the 75% concentration exhibited a larvicidal effect against both mosquito larval types. Turmeric rhizome infusion (Curcuma longa L.) was proven to have inhibitory activity against Aedes sp. larvae, although its effectiveness was still lower than that of chemical larvicides. However, the community considered the use of turmeric rhizome infusion safer, simpler, and easier to apply than natural larvicides. Therefore, this study can serve as a reference for developing natural larvicidal agents from turmeric rhizomes (Curcuma longa L.).